SUPRAMOLECULAR CRYSTALLIZATION IN MINERAL FORMATION PROCESSES - Kalinin D.V.; Serdobintseva V.V. (My University, 2001)
The process of formation of colloidal and metacolloidal minerals, which can give rise to monodisperse systems, is considered in the context of supramolecular crystallization. We present data on synthesis of monodisperse particles: oxides, hydroxides, sulfides, etc. The general regularities of supramolecular crystallization under experimental conditions and in nature are analyzed.